Religion, Faith and Empowerment: Hindu Women’s Agency and Sacred Spaces in Far-West Nepal - Joshi, Yashoda Kumari Bhatta (Ganeshman Darpan, 2026)
Contrary to dominant development narrative that views religion as an obstructing force, this study highlights how local religious spaces, family rituals, and festival-specific celebrations provide Hindu women in Far-West Nepal distinct pathways to assert agency, build protective social networks, and re-define their status. Explaining the deep-rooted religious practices, like daily household worships, weekly fasts, temple singing and dancing groups, and observance of wide-ranging festivals, the paper examines how religiosity acts as a vital platform in power game of life. By reviewing the local field evidence on regional gender and celebratory customs, this study provides a comprehensive qualitative finding that the assertive presence of Hindu women in domestic and public religious spaces allows them challenge gender stereotypes and accumulate social capital despite structural patriarchal barriers. This article lastly argues that understanding Hindu women’s psycho-social empowerment in Far-West Nepal requires a culturally sensitive approach that recognizes transformative potential of everyday religiosity.